Study protocol to support the development of an all-night binaural beat frequency audio program to entrain sleep - Gantt, Melisa A. (Frontiers in Neurology, 2023)
Background Given that the stages of sleep have specific brainwave patterns, it may be feasible to manipulate brainwaves to induce stages of sleep to improve better sleep quality. Binaural beat frequencies (BBFs) are an auditory-neurologic technique that uses auditory tones via headphones to manipulate brainwave activity in turn affecting the listener's state of consciousness. However, BBFs are often sold in only one frequency which may not allow the listener to transition through the phases of sleep. This study is Phase 2 of a four-phase feasibility study to assess if systematically sequencing a variety of BBFs can improve sleep efficiency. Methods This protocol uses a two cohort unblinded and double-blinded, randomized, pre- and post-intervention methods and crossover matched group design. In Cohort 1, a sample of 106 participants with poor sleep quality will be randomized into two groups. All participants will start with 1 week of no intervention. Group 1 will use theta/delta BBF for 2 weeks followed by 1 week of no intervention followed by music for 2 weeks. Group 2 will do the reverse. In Cohort 2, 62 participants will be blinded and randomized into two groups. Group 3 will use music for 2 weeks followed by a 1-week break followed by music embedded with theta/delta BBF for 2 weeks. Group 4 will do the reverse. Using Cohort 1 music only as a control, data will be collected using sleep actigraphy, sleep quality questionnaires, and sleep diaries with a crossover and match group analysis between cohorts to compare the effect of no intervention vs. music vs. BBF only vs. music with BBF on sleep quality. Discussion Phase 1 concluded that theta BBF was able to decrease stress to help induce sleep. Phase 2 will assess if theta and delta BBFs, with breaks to allow for REM, will be able to sustain sleep to improve sleep efficiency. The data from Phase 1 and 2 will provide information to help construct an all-night audio program with the appropriate BBF and timing to trigger the correct sleep stage for better sleep efficiency. If this concept is feasible, it could be beneficial for many sleep disorders.